Factors that influence the length of hospitalization for acute heart failure patients in RSUP Dr. M Djamil - M. Syaoqi; Andri Andri; Citra Kiki Krevani; Muhammad Syukri (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
More than 500,000 new patients were diagnosed with heart failure each year in all developing countries. Previous studies had shown that longer hospitalizations for patients with acute heart failure are associated with worse outcome. We analyzed factors that influence length of stay in our centre. We used a retrospective and descriptive analysis of acute heart failure patients at RSUP DR. M. Djamil from January to March 2018. We collected patient data from medical records including baseline characteristics, laboratory and echocardiographic results. We used statistical analysis to find the average length of stay (LOS) and possible causes of longer hospitalization. Among 30 patients had been collected, mean LOS was 6.23 days. Mean for age, BMI, and LVEF were 59.87 years, 23.55 kg/m2, and 36.93%, respectively. Patients those had LOS > 6 days may had relationship with initial degree edema pretibial (p=0.025) and systolic BP below 120 mmHg (p=0.018), but no significant with rales (p=0.543) and pulmonary infection (p=0.709). Length of stay associated with the degree of pretibial pitting edema and systolic blood pressure at admission.